The Separation of Ownership and Control in American Industry - Means, Gardiner C. (Quarterly Journal of Economics, 1931)
Introduction. The concept “control.” — Types of control; complete ownership, 72; majority control, 73; legal device, 74; minority control, 81; and management control, 83. — Separation of ownership and control among the 200 largest American corporations; basis of classification and extent of separation, 89. — Conclusion, 95. — Tables showing types of control, 98.